Effect of Sr doped the YFeO3 rare earth ortho-ferrite on structure, magnetic properties, and microwave absorption performance. Issue 24 (15th December 2021) - Wang, Man; Cheng, Lichun; Huang, Lei; Pan, Shunkang; Yao, Qingrong; Hu, Chaohao; Liang, Qihua; Zhou, Huaiying
Abstract: Given the remarkable performances of rare earth multiferroic ortho-ferrites with magnetic optical and dielectric properties, the Y1- x Sr x FeO3 ( x  = 0, 0.05, 0.1, 0.15) perovskite structure microwave absorbing ferrite materials was successfully synthesized by Sr 2+ ions A-site doping based on sol-gel technology in this paper. The XRD of all samples was refined with FullProf software, which confirmed the formation of the orthogonal perovskite structure (SG: Pnma ). The SEM and TEM results display the average particles size of the samples is distributed between 110 and 160 nm. The increase of Sr doping concentration leads to the increase of particles size, which may be related to the growth of preferred orientation and incomplete substitution. The XPS analysis shows that Fe 3+ was accompanied by the presence of Fe 2+ with the doping of Sr 2+ ions and oxygen vacancies increased significantly. The samples change from weak ferromagnetic state to paramagnetic state with the increase of Sr content. The minimum reflection loss ( RL ) of the Y0.95 Sr0.05 FeO3 samples at 12.2 GHz reached −30.87 dB with thickness of 2.2 mm, where its effective absorption bandwidth (EAB, RL  ≤ −10 dB) reached 2.4 GHz (11.3–13.7 GHz). Moreover, the EAB of the Y0.85 Sr0.15 FeO3 samples reached 2.64 GHz, and the corresponding range is 9.0–11.6 GHz (X-band).